Replication of the scrapie agent in ocular neural tissues. - Buyukmihci, N (1980)
Optic nerves and retinas removed from hamsters experimentally inoculated with the scrapie agent contain a high titer of infectivity. Ophthalmoscopic examination of these animals revealed gross lesions of retinopathy as early as 3 weeks before the onset of clinical signs of brain degeneration. These results suggest that the scrapie agent may spread centrifugally in nerve fibers after intracerebral inoculation and that the scrapie-associated retinopathy seen in hamsters is directly induced by the agent rather than the result of retrograde degeneration from central neural damage.